Child-friendly Justice and Procedural Safeguards For Children in Criminal Proceedings: New Momentum for Children in Conflict with the Law? - Ton Liefaard (Bergen Journal of Criminal Law and Criminal Justice, 2020)
Child-friendly justice has its focus on on the effective participation of children in justice systems. During the past decade the concept, grounded in international children’s rights, has become meaningful for justice systems in Europe and beyond. Despite its flaws and gaps, it has the potential of making justice systems more accessible for children, including the (juvenile) criminal justice system with its particular complexity. However, in order to understand its true potential more research is needed. This article elaborates on the concept of child-friendly justice and sheds light on a research agenda around its core elements.